Citation Practices in Selected Science and Humanities Dissertations: Implications for Teaching - Maroko, Geoffrey M. (American Journal of Educational Research, 2013)
The citation feature provides justification for arguments and demonstrates the novelty of one’s position in research writing. It shows how a piece of research arises out of, and is grounded in the current state of disciplinary knowledge. As such, research supervisors encourage the candidates under their guidance to make citations especially when writing literature reviews and discussion sections of their dissertations. This requirement plunges many a student in confusion on how to go about this integral undertaking without written citation norms in their disciplines. The question that emerges is: On which benchmarks should dissertation writers base their citations when writing dissertations in their disciplines? Put in other words, on which benchmarks should research supervisors base their judgement on the quality of citations in their students’ dissertations? The aim of this paper therefore is to uncover citation practices in selected Humanities and Science dissertations from Kenyan public universities. The paper analyses the citation types and reporting verbs of choice employed in Humanities dissertations and compares them with those in the Science dissertations. Consequently, the paper proposes a set of citation norms that can inform the writing of the Humanities and Sciences dissertation and suggests a genre-based approach for raising students’ consciousness to the citation norms during the drafting stage of their dissertations.
Keywords: Citation; Integral and non-integral citations; Norms